2020
DOI: 10.3390/molecules25173831
|View full text |Cite
|
Sign up to set email alerts
|

Caesalpinia ferrea C. Mart. (Fabaceae) Phytochemistry, Ethnobotany, and Bioactivities: A Review

Abstract: Caesalpinia ferrea C. Mart., popularly known as “Jucá” or “Pau-ferro”, belongs to the Fabaceae family, and is classified as a native and endemic species in Brazil. Numerous studies that portray its ethnobotany, chemical composition, and biological activities exist in the literature. The present study aimed to systematically review publications addressing the botanical aspects, uses in popular medicine, phytochemical composition, and bioactivities of C. ferrea. The searches focused on publications from 2015 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 85 publications
0
17
0
2
Order By: Relevance
“…The antifungal potential of Poincianella ( Caesalpinia ) species has been previously described. Different parts of Caesalpinia sappan ( Niranjan Reddy et al, 2003 ), Caesalpinia pyramidalis ( Cruz et al, 2007 ), Caesalpinia bonducella ( Shukla et al, 2011 ), Caesalpinia ferrea Martius ( Macêdo et al, 2020 ), and Caesalpinia pulcherrima ( de Melo et al, 2020 ) showed antifungal effect in vitro against planktonic cells of several fungal species, which can cause infections in humans such as Trichophyton rubrum , Candida guilliermondii , Candida albicans , Candida parapsilosis , and Fonsecaea pedrosoi . Among these plant species, the inhibitory activity of only two species was evaluated on growth of planktonic cells of C. neoformans .…”
Section: Discussionmentioning
confidence: 99%
“…The antifungal potential of Poincianella ( Caesalpinia ) species has been previously described. Different parts of Caesalpinia sappan ( Niranjan Reddy et al, 2003 ), Caesalpinia pyramidalis ( Cruz et al, 2007 ), Caesalpinia bonducella ( Shukla et al, 2011 ), Caesalpinia ferrea Martius ( Macêdo et al, 2020 ), and Caesalpinia pulcherrima ( de Melo et al, 2020 ) showed antifungal effect in vitro against planktonic cells of several fungal species, which can cause infections in humans such as Trichophyton rubrum , Candida guilliermondii , Candida albicans , Candida parapsilosis , and Fonsecaea pedrosoi . Among these plant species, the inhibitory activity of only two species was evaluated on growth of planktonic cells of C. neoformans .…”
Section: Discussionmentioning
confidence: 99%
“…Based on these models, medicinal plants have been reported to possess numerous secondary metabolites with potent anti-inflammation effects and demonstrated therapeutic promises for inflammation-related diseases [21]. Therefore, medicinal plants are important resources of anti-inflammatory compounds [22]. And our previous studies confirmed that the ethanol extract of Bletilla striata has the preventive and therapeutic effect on silicainduced pulmonary fibrosis in rats [15].…”
Section: Introductionmentioning
confidence: 94%
“…e uncontrolled inflammatory responses are closely associated with the development of inflammatory diseases. Hence, antiinflammatory compounds with the ability to inhibit the expression of inflammatory proteins and genes and the production of proinflammatory markers are an efficient way to control inflammatory diseases [13][14][15][16][17][18][19][20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%